ROCHA, Christina; VÁSQUEZ, Manuel A. (orgs.). The diaspora of Brazilian religions - Engler, Steven (REVER: Revista de Estudos da Religião, 2014)
Resenha do livro: ROCHA, Christina; VÁSQUEZ, Manuel A. (orgs.). The diaspora of Brazilian religions. Leiden e Boston, Brill, 2013, ISBN 978-90-04-23694-3, 391 p.